Electrochemical oxygen reduction catalyst
Patent Information
- Application Number
- CN202511921918.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-09
- Filing Date
- 2025-12-18
- Publication Date
- 2026-10-16
AI Technical Summary
[0028] According to the present invention, an electrochemical oxygen reduction catalyst exhibiting high catalytic activity and a high catalytic activity enhancement effect can be provided.
Smart Images

Figure CN122930928A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to electrochemical oxygen reduction catalysts. Background Technology
[0002] Electrochemical oxygen reduction catalysts are widely used in fuel cells, water electrolysis systems, metal-air batteries, and other applications. As electrochemical oxygen reduction catalysts, catalysts modified with nitrogen-containing organic compounds on a supported catalyst metal are known.
[0003] For example, Patent Document 1 discloses a catalyst characterized by comprising metal particles with oxygen reduction activity, an additive with basic functional groups, and a binder with acidic functional groups, wherein the additive is at least one organic nitrogen compound, and the ratio of the total amount of basic functional groups of the additive to the total amount of acidic functional groups of the binder (basic point amount / acid point amount) is greater than 0 and less than 6.82. Patent Document 1 discloses that the metal particles can be supported on a carrier.
[0004] Furthermore, Patent Document 2 discloses a catalyst characterized by comprising oxygen-reducing metal particles, a support, and an additive, wherein the metal particles are supported on the support, the additive is at least one organic nitrogen compound, and the support has a BET specific surface area of 641 m². 2 g -1 载体 the following.
[0005] [Existing Technical Documents]
[0006] [Patent Literature]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 2024-11754
[0008] [Patent Document 2] Japanese Patent Application Publication No. 2024-16321 Summary of the Invention
[0009] [The problem the invention aims to solve]
[0010] As described above, electrochemical oxygen reduction catalysts comprising a catalyst metal supported on a carrier are known. However, in conventional catalysts, depending on the carrier used, sometimes the sufficiently enhanced catalytic activity resulting from modifying the catalyst metal with additives cannot be obtained; furthermore, high catalytic activity is sometimes not achieved. Therefore, the object of the present invention is to provide an electrochemical oxygen reduction catalyst exhibiting both high catalytic activity and a significant enhancement of catalytic activity.
[0011] [Methods used to solve problems]
[0012] The inventors discovered that by controlling the characteristics of mesoporous carbon supports, the catalytic activity and the catalytic effect can be improved, thus completing this invention.
[0013] That is, the present invention includes the following aspects and embodiments.
[0014] (Embodiment 1) An electrochemical oxygen reduction catalyst, comprising an oxygen reduction active catalyst metal supported on mesoporous carbon and a modification layer modifying the catalyst metal.
[0015] The mesoporous carbon has a main particle size of less than 700 nm and the mesoporous carbon satisfies at least one of the following conditions a) to c):
[0016] a) BET specific surface area is greater than 641m² 2 g -1 ;
[0017] b) The mode aperture is less than 7.7 nm;
[0018] c) The total micropore capacity of pores in the range of 2.0 nm to 30 nm is greater than 6.50 mL g. -1 .
[0019] (Embodiment 2) According to the electrochemical oxygen reduction catalyst of Embodiment 1, wherein the mode particle size of the primary particles of the mesoporous carbon is less than 300 nm.
[0020] (Embodiment 3) An electrochemical oxygen reduction catalyst, comprising an oxygen reduction active catalyst metal supported on mesoporous carbon and a modification layer modifying the catalyst metal.
[0021] The mesoporous carbon has a median primary particle size of less than 750 nm, and the mesoporous carbon satisfies at least one of the following conditions a) to c):
[0022] a) BET specific surface area is greater than 641m² 2 g -1 ;
[0023] b) The mode aperture is less than 7.7 nm;
[0024] c) The total micropore capacity of pores in the range of 2.0 nm to 30 nm is greater than 6.50 mL g. -1 .
[0025] (Embodiment 4) The electrochemical oxygen reduction catalyst according to Embodiment 3, wherein the median particle size of the primary particles of the mesoporous carbon is less than 400 nm.
[0026] (Embodiment 5) An electrochemical oxygen reduction catalyst according to any one of Embodiments 1 to 4, wherein the catalyst metal is platinum, a platinum alloy or a platinum-containing composite, and the modification layer contains a nitrogen-containing cyclic organic compound or a polymer thereof or their cations.
[0027] Invention Effects
[0028] According to the present invention, an electrochemical oxygen reduction catalyst exhibiting high catalytic activity and a high catalytic activity enhancement effect can be provided. Attached Figure Description
[0029] Figure 1 This is a graph showing the relationship between the mode particle size of the primary particles of the carbon support and the rate of increase in the mass activity of the catalyst.
[0030] Figure 2 This is a graph showing the relationship between the median particle size of the primary particles of the carbon support and the rate of increase in the mass activity of the catalyst. Detailed Implementation
[0031] The preferred embodiments of the present invention will now be described in detail.
[0032] <Electrochemical Oxygen Reduction Catalyst>
[0033] One aspect of the present invention relates to an electrochemical oxygen reduction catalyst. The electrochemical oxygen reduction catalyst of this aspect (hereinafter also referred to as the catalyst of this aspect) comprises an oxygen-reducing catalyst metal supported on mesoporous carbon and a modifying layer modifying said catalyst metal. That is, the catalyst of this aspect comprises a mesoporous carbon support, an oxygen-reducing catalyst metal, and a modifying layer.
[0034] In a first embodiment of the catalyst in this aspect, the mode particle size of the primary particles of mesoporous carbon is less than 700 nm.
[0035] In a second embodiment of the catalyst in this aspect, the median particle size of the primary particles of mesoporous carbon is less than 750 nm.
[0036] The configurations of the first and second embodiments of the catalyst in this regard will be described below.
[0037] In this type of catalyst, the catalyst metal can be any metal that exhibits oxygen reduction activity (oxygen reduction catalytic ability). Examples of catalyst metals include platinum, ruthenium, iridium, rhodium, palladium, osmium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium. The catalyst metal may consist of one of the illustrated metals alone or in the form of an alloy of two or more. Furthermore, the catalyst metal may be an oxide, nitride, sulfide, or phosphide of the illustrated metal. Platinum, platinum alloys, or platinum-containing complexes are preferred as the catalyst metal. In the case of platinum alloys and platinum complexes, metals other than platinum, such as ruthenium, iridium, and cobalt, can be used as examples. When the catalyst metal is a platinum alloy or a platinum-containing complex, the content of metals other than platinum is typically in the range of 0.11 atomic% to 60 atomic% relative to the total mass of the catalyst metal.
[0038] The loading ratio of catalyst metal relative to the mass of mesoporous carbon is typically in the range of 1% to 70% by mass, for example, in the range of 18% to 48% by mass.
[0039] The particle size of catalyst metals is typically in the range of 1 nm to 100 nm.
[0040] In the catalysts of this aspect, the composition and content of the catalyst metal can be determined, for example, by analysis using thermogravimetric analysis (TG) or high-frequency inductively coupled plasma atomic emission spectroscopy (ICP).
[0041] In this type of catalyst, the particle size of the catalyst metal can be determined, for example, by measuring the crystallite diameter using X-ray diffraction and calculating the average crystallite diameter. Alternatively, the particle size of the catalyst metal can be determined by measuring the particle size of 100 to 1000 catalyst metal particles using electron microscopy and calculating their average value (average particle size).
[0042] In the catalysts of this aspect, the catalyst metal is supported on mesoporous carbon (carbon support). In this disclosure, mesoporous carbon is carbon having fine pores. In the catalysts of this aspect, the catalyst metal is typically supported inside the fine pores of the mesoporous carbon, and may also be supported on the surface of the mesoporous carbon. In one embodiment, the catalyst metal is supported both inside the fine pores of the mesoporous carbon and on the surface of the mesoporous carbon.
[0043] As a method for loading catalyst metal onto mesoporous carbon, conventional methods can be employed. For example, the following method can be used: The catalyst metal is mixed into a mesoporous carbon dispersion containing mesoporous carbon, filtered, washed, and then dispersed in ethanol or the like, followed by drying using a vacuum pump or similar method. After drying, heat treatment can be performed as needed.
[0044] In this type of catalyst, mesoporous carbon comprises primary particles with fine pores. A primary particle is the smallest unit of an indivisible particle. Mesoporous carbon may contain only primary particles with fine pores, or it may contain secondary particles formed by the aggregation of primary particles with fine pores. The presence of fine pores in the primary particles can be confirmed, for example, by observation using an electron microscope.
[0045] In the first embodiment of the catalyst of this aspect, the modal particle size of the primary particles of mesoporous carbon is 700 nm or less. If the catalyst metal is supported inside the fine pores of the support, the distance from the support surface to the catalyst metal becomes longer, making it difficult to modify the catalyst metal with a modification layer containing additives, and thus difficult to exhibit an improved catalytic activity effect. When the modal particle size of the primary particles of mesoporous carbon is 700 nm or less, it becomes easier to modify the catalyst metal with a modification layer, and the catalytic activity improvement effect is enhanced. The modal particle size of the primary particles of mesoporous carbon can be 300 nm or less, or 100 nm or less, or 50 nm or less. When the modal particle size of the primary particles of mesoporous carbon is within this range, the catalytic activity improvement effect is further enhanced. The lower limit of the modal particle size of the primary particles of mesoporous carbon is not particularly limited, for example, it can be 5 nm or more, or 10 nm or more, or 20 nm or more. The modal particle size of the primary particles of mesoporous carbon can be, for example, 5 nm to 700 nm, or 10 nm to 300 nm. The mode size of primary particles of mesoporous carbon refers to the particle size (also known as the peak size) that has the highest peak value in the particle size distribution (number basis) obtained by the determination method described below.
[0046] In a second embodiment of the catalyst of this aspect, the median particle size of the primary particles of mesoporous carbon is 750 nm or less. When the median particle size of the primary particles of mesoporous carbon is 750 nm or less, it is easier to modify the catalyst metal with a modification layer, thereby improving the catalyst activity. The median particle size of the primary particles of mesoporous carbon can be 400 nm or less, or 350 nm or less, or 80 nm or less. When the median particle size of the primary particles of mesoporous carbon is within this range, the catalytic activity is further improved. The lower limit of the median particle size of the primary particles of mesoporous carbon is not particularly limited, for example, it can be 5 nm or more, or 10 nm or more, or 20 nm or more. The median particle size of the primary particles of mesoporous carbon can be, for example, 5 nm to 750 nm, or 10 nm to 400 nm. The median particle size of the primary particles of mesoporous carbon refers to the 50% cumulative particle size (also called D50) in the particle size distribution (number basis) obtained by the measurement method described below.
[0047] The mode and median particle sizes of primary particles of mesoporous carbon can be determined using methods such as transmission electron microscopy (TEM), scanning electron microscopy (SEM), laser diffraction, light scattering, dynamic light scattering (DLS), centrifugation, and particle trajectory analysis (PTA). These methods can also be combined. For example, the particle size of 100 to 1000 primary particles of mesoporous carbon can be determined using TEM or SEM, and the mode and median particle sizes in the resulting particle size distribution can be used as the mode and median particle sizes of the primary particles of the mesoporous carbon, respectively. In one embodiment, the mode and median particle sizes of the primary particles of mesoporous carbon can be determined using both TEM and laser diffraction.
[0048] In one embodiment, the mesoporous carbon may have both the mode particle size of the primary particles in the first embodiment and the median particle size of the primary particles in the second embodiment. That is, in one embodiment, the mode particle size of the primary particles of the mesoporous carbon is 700 nm or less, and the median particle size of the primary particles is 750 nm or less.
[0049] In the catalysts of this aspect, the mesoporous carbon satisfies at least one of the following: a) to c)
[0050] a) BET specific surface area is greater than 641m² 2 g -1 ;
[0051] b) The mode aperture is less than 7.7 nm;
[0052] c) The total micropore capacity of pores in the range of 2.0 nm to 30 nm is greater than 6.50 mL g. -1 .
[0053] Among them, mesoporous carbon can satisfy 1, 2 or 3 of a) to c), or 2 or 3. In one embodiment, it satisfies 3 (all) of a) to c).
[0054] Regarding a) above, the BET specific surface area of mesoporous carbon can be greater than 641 m². 2 g -1 Greater than 650m 2 g -1 In this regard, the catalytic activity of the catalyst increases when the BET specific surface area of the mesoporous carbon is within this range. Furthermore, the BET specific surface area is a value relative to the mass of the mesoporous carbon (m). 2 g -1 介孔碳 ).
[0055] Regarding b) above, the mode pore size of mesoporous carbon can be less than 7.7 nm or less than 7.0 nm. In the catalysts of this aspect, the catalytic activity increases when the mode pore size of the mesoporous carbon is within this range. Furthermore, pore size refers to the diameter of the pores. Additionally, the mode pore size of mesoporous carbon refers to the pore size with the highest peak value (also called the peak pore size) in the pore distribution curve obtained by the measurement method described below.
[0056] Regarding c) above, the total micropore capacity of mesoporous carbon in the range of 2.0 nm to 30 nm can be greater than 6.50 mL g. -1 Greater than 7.0 mL g -1 In the catalysts of this aspect, the catalytic activity increases when the total micropore capacity of the mesoporous carbon falls within this range. The total micropore capacity refers to the total micropore capacity (mL / g) of pores with a diameter in the range of 2.0 nm to 30 nm relative to the mass of the mesoporous carbon. -1 介孔碳 ).
[0057] Regarding the physical properties of mesoporous carbon (support), the support itself can be measured directly, or the support loaded with catalyst metal can be measured and converted into the mass of the support. The BET specific surface area, mode pore size, and total pore capacity in the 2.0 nm–30 nm range can all be determined by N2 adsorption-desorption. Alternatively, these three parameters can be obtained based on the relative pressure dependence of N2 adsorption on the sample. The BET theory is used in the specific surface area calculation. Evaluation methods are not limited to the above methods; they can also be evaluated based on the Hg porosity method, H2O adsorption method, and the oil absorption of DBP using dibutyl phthalate. Microscopic observation can also be used.
[0058] In the catalyst of this aspect, the content of mesoporous carbon can be determined, for example, by analysis using thermogravimetric analysis (TG) or high-frequency inductively coupled plasma atomic emission spectroscopy (ICP).
[0059] In the catalyst of this aspect, the modifying layer may contain a nitrogen-containing cyclic organic compound or a polymer thereof or their cations. In the catalyst of this aspect, a nitrogen-containing cyclic organic compound or a polymer thereof or their cations are used as an additive (modifier), and the catalyst metal is modified by a modifying layer containing the additive, thereby promoting the electrochemical oxygen reduction reaction.
[0060] In the catalysts of this aspect, the nitrogen-containing cyclic organic compound can be, for example, a compound having one, two, three, four, or five nitrogen atoms within the ring, and possessing a 3-membered to 20-membered or 3-membered to 10-membered ring, or a compound having a 5- or 6-membered ring. The nitrogen-containing cyclic organic compound can be monocyclic or polycyclic. When the nitrogen-containing cyclic organic compound is polycyclic, it is sufficient that at least one ring has a nitrogen atom. The nitrogen-containing cyclic organic compound is not particularly limited, and examples include piperidine, piperazine, morpholine, quinine ring, pyrrolidine, azacyclobutane, azacyclobutane-2-one, aziridine, cycloheptane, pyrrole, imidazole, pyrazole, oxazole, isoxazole, thiazole, isothiazazole, pyridine, pyrimidine, pyrazine, triazine, quinoline, isoquinoline, quinazoline, phthalazine, pteridine, 1,4-benzodiazepine, indole, benzimidazole, purine, acridine, phenoxazine, phenothiazine and their derivatives, as well as some organic compounds containing their skeletons. In one embodiment, from the viewpoint of durability, the nitrogen-containing cyclic organic compound is a compound having a triazine skeleton (1,2,3-triazine, 1,2,4-triazine or 1,3,5-triazine).
[0061] In one embodiment, the nitrogen-containing cyclic organic compound or its polymer or their cation is a compound represented by general formula (1), or a polymer with the compound as a monomer, or their cation.
[0062] [Chemical Formula 1]
[0063]
[0064] (In the formula, R1, R2, and R3 are each selected from one of the following functional groups: hydrogen atom, halogen atom, nitrile group, amide group, imine group, amino group, thiol group, hydroxyl group, sulfonyl group, carboxylic acid group, phosphate group, ketone group, aldehyde group, ester group, alkoxy group, phenolic group, cyclopentyl group, cyclohexyl group, alkylamino group with 1 to 10 carbon atoms, alkylsulfonic acid group with 1 to 10 carbon atoms, perfluoroalkyl group with 1 to 10 carbon atoms, alkyl group with 1 to 10 carbon atoms, alkenylamino group with 2 to 10 carbon atoms, alkenylsulfonic acid group with 2 to 10 carbon atoms, perfluoroalkenyl group with 2 to 10 carbon atoms, and alkenyl group with 2 to 10 carbon atoms. The functional group may have at least one of the following functional groups selected from the group of said functional groups, aromatic ring, heterocycle, oxygen atom, sulfur atom, nitrogen atom, fluorine atom, chlorine atom, bromine atom, iodine atom, and hydrogen atom in the molecular chain.)
[0065] Nitrogen-containing cyclic organic compounds or their polymers or their cations (hereinafter also referred to as nitrogen-containing cyclic organic compounds, etc.) may be melamine (1,3,5-triazine-2,4,6-triamine), carbamic acid, cyanuric acid, triazine (1,2,3-triazine, 1,2,4-triazine or 1,3,5-triazine) or their derivatives, polymers thereof, or their cations. Alternatively, the nitrogen-containing cyclic organic compound, etc., can be 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine, 6-(dibutylamino)-1,3,5-triazine-2,4-dithiol, 2,4-diamino-6-butylamino-1,3,5-triazine, or 2,4,6-tris(pentafluoroethyl)-1,3,5-triazine, or polymers thereof as monomers, or copolymers such as melamine-formaldehyde copolymers such as methylated poly(melamine-co-formaldehyde) or isobutylated poly(melamine-co-formaldehyde), or their cationic forms. In one embodiment, the nitrogen-containing cyclic organic compound, etc., is melamine or a derivative thereof, a polymer thereof, or their cationic forms.
[0066] The content of the modification layer, expressed as a mass ratio relative to the mass of the catalyst metal in the catalyst of this aspect, is typically in the range of 0.001 to 0.1.
[0067] The composition and content of nitrogen-containing cyclic organic compounds or their polymers or their cations contained in the modified layer can be determined, for example, by dissolving and extracting the modified layer contained in the catalyst of this aspect, and analyzing the components contained in the extract using elemental analysis, various chromatographic methods, ultraviolet-visible spectrophotometry (UV-Vis), infrared spectrophotometry (IR), or nuclear magnetic resonance (NMR).
[0068] In the catalysts of this aspect, the modification layer is typically disposed on the surface of the catalyst metal, for example, coating the surface of the catalyst metal. The modification rate of the modification layer on the surface of the catalyst metal relative to the total surface area of the catalyst metal can be 8 area % or more, or 11 area % or more, 12 area % or more, or 20 area % or more. When the modification rate is 8 area % or more, the catalyst activity is improved. There is no particular upper limit to the modification rate of the modification layer on the surface of the catalyst metal, for example, it can be 50 area % or less, or 40 area % or less, or 30 area % or less. The modification rate of the modification layer on the surface of the catalyst metal is defined as the percentage of the surface area of the catalyst metal modified by the modification layer relative to the total surface area of the catalyst metal. The modification rate of the modification layer on the surface of the catalyst metal can be determined, for example, by the method described in the examples.
[0069] The catalyst in this respect may include a binder. The binder is typically a polymeric electrolyte (ionomer) containing ion-exchange groups. Examples of ion-exchange groups contained in the polymeric electrolyte include sulfonic acid groups and phosphoric acid groups. The binder may be, for example, a perfluorocarbon sulfonic acid polymer.
[0070] Applications of Electrochemical Oxygen Reduction Catalysts
[0071] Another aspect of the present invention relates to a fuel cell. The fuel cell of this aspect has at least a cathode electrode catalyst layer, an anode electrode catalyst layer, and an electrolyte membrane disposed between the cathode electrode catalyst layer and the anode electrode catalyst layer, wherein the cathode electrode catalyst layer comprises an electrochemical oxygen reduction catalyst according to one aspect of the present invention.
[0072] Another aspect of the present invention relates to a water electrolysis system. The water electrolysis system of this aspect includes at least a cathode electrode catalyst layer, an anode electrode catalyst layer, an electrolyte membrane disposed between the cathode electrode catalyst layer and the anode electrode catalyst layer, and a water supply unit, wherein the anode electrode catalyst layer comprises an electrochemical oxygen reduction catalyst according to one aspect of the present invention.
[0073] Another aspect of the present invention relates to a metal-air battery. The metal-air battery of this aspect has at least an electrode catalyst layer for a cathode, a metal layer for an anode, and an electrolyte membrane disposed between the electrode catalyst layer for the cathode and the metal layer for the anode, wherein the electrode catalyst layer for the cathode comprises an electrochemical oxygen reduction catalyst according to one aspect of the present invention.
[0074] <Methods for Manufacturing Electrochemical Oxygen Reduction Catalysts>
[0075] Another aspect of the present invention relates to a method for manufacturing an electrochemical oxygen reduction catalyst according to one aspect of the present invention. The method of this aspect includes a modification step. The method of this aspect may, as needed, include a preparation step and an electrode catalyst layer fabrication step.
[0076] [Preparation Process]
[0077] This process includes preparing mesoporous carbon (support), catalyst metal, and additives. This process typically also includes preparing a binder. Furthermore, this process may, as needed, include preparing additional materials such as solvents and substrates. Each material prepared in this process only needs to possess the characteristics described above. In this process, each material can be prepared by hand to obtain materials with the specified characteristics, or commercially available products can be purchased. The catalyst metal can be loaded onto the mesoporous carbon using conventional methods. It should be noted that loading the catalyst metal onto the mesoporous carbon can be achieved by mixing the mesoporous carbon, catalyst metal, and additives in a subsequent modification process.
[0078] [Finishing Process]
[0079] This step involves mixing a catalyst metal supported on mesoporous carbon with an additive, and then modifying the catalyst metal with a modification layer containing the additive. In this step, a binder may also be mixed together, if desired, in addition to the catalyst metal and the additive. Typically, the catalyst metal supported on mesoporous carbon, the additive, and the binder, if desired, are mixed with a solvent. The solvent is not particularly limited; examples include water and alcohols (e.g., 2-propanol), and mixtures of more than one of these.
[0080] In this process, by removing the solvent from the resulting mixture, an electrochemical oxygen reduction catalyst of one aspect of the present invention can be obtained.
[0081] Alternatively, when performing the electrode catalyst layer fabrication process described below, the mixture obtained in this process can be used as a catalyst ink containing an electrochemical oxygen reduction catalyst according to one aspect of the present invention in the electrode catalyst layer fabrication process. In this case, the mixture obtained in this process can be used as is, or it can be used with the solvents shown in the example added.
[0082] [Electrode Catalyst Layer Fabrication Process]
[0083] This process involves applying a catalyst ink containing an electrochemical oxygen reduction catalyst, obtained in the modification process, to the surface of a substrate. In this process, solvent is typically removed from the coated catalyst ink.
[0084] There are no particular limitations on the substrate used in this process; any material such as polytetrafluoroethylene (PTFE), electrolyte membranes with ion exchange groups, carbon fibers, and metal fibers can be used.
[0085] By performing this process, an electrochemical oxygen reduction catalyst of one aspect of the present invention can be obtained in the form of an electrode catalyst layer disposed on the surface of a substrate. In this case, the film thickness of the electrode catalyst layer is typically in the range of 5 μm to 30 μm. Furthermore, the content of the catalyst metal in the electrode catalyst layer, based on the mass relative to the total area of the electrode catalyst layer, is typically 0.1 to 0.6 mg / cm³. 2 The range.
[0086] [Example]
[0087] The present invention will now be described in more detail using examples. However, the scope of the present invention is not limited to these examples.
[0088] <Preparation of Electrochemical Oxygen Reduction Catalysts>
[0089] [Examples 1-7 and Comparative Examples 1-7]
[0090] Mesoporous carbons (carbon supports) with different properties as shown in Table 1 were prepared. The BET specific surface area, mode pore size, and total pore volume of the carbon supports in the range of 2.0 nm to 30 nm were determined as described above. The mode and median particle sizes of the primary particles of the carbon supports were determined using transmission electron microscopy (TEM) and laser diffraction as reference values.
[0091] Platinum particle support carriers are prepared, in which platinum particles are loaded onto various carbon supports.
[0092] A specified amount of the above-mentioned support loaded with platinum particles, melamine (additive), perfluorocarbon sulfonate polymer (Nafion (Chemours) base, EW: 1100), 2-propanol, and ultrapure water were added to a container, mixed, and stirred to prepare a catalyst ink containing an electrochemical oxygen reduction catalyst. In the electrochemical oxygen reduction catalyst, the platinum particles are modified by a melamine-containing modification layer.
[0093] Evaluation of Electrochemical Oxygen Reduction Catalysts
[0094] [Catalytic performance]
[0095] The catalyst mass activity (Ag) at a potential of 0.9V (vs. RHE) was determined by... -1 To evaluate catalyst performance, catalyst mass activity is expressed as the current per unit mass of metal particles; a higher value indicates higher catalyst activity.
[0096] Catalyst ink was drop-added onto a glassy carbon rotating electrode (5 mm in diameter) (manufactured by Beidou Electric Co., Ltd.) to achieve a carrier content of 20 μg cm⁻¹. -2 The material is dried to create an electrode with a catalyst layer on its surface.
[0097] The fabricated electrode was used as the working electrode, the reversible hydrogen electrode as the reference electrode, and the carbon rod as the counter electrode for electrochemical measurements in a three-electrode configuration. Electrochemical measurements were performed using the rotating electrode method (RDE). A 0.1 M perchloric acid aqueous solution adjusted to ultrapure water was used as the electrolyte. After cyclic voltammetry under an inert gas atmosphere, the atmosphere was changed to oxygen, and linear sweep voltammetry was performed from the low potential side. The electrode rotation speed was changed to 400, 900, 1600, 2000, 2500, and 3600 rpm, and linear sweep voltammetry was repeated. Koutechey-Levich plots were constructed from the obtained potential-current characteristics, and the catalyst mass activity (Ag) at 0.9 V (vs. RHE) was calculated. -1The following formula was used to calculate the ratio (catalyst activity increase factor) by modifying the catalyst with a modification layer containing the additive: (catalyst activity value after additive introduction) / (catalyst activity value before additive introduction). Additionally, based on the potential-current characteristics, a current density of 0.2 A cm⁻¹ was recorded. -2 The battery potential (battery voltage) at that time.
[0098] [Surface Modification Rate]
[0099] For electrochemical oxygen reduction catalysts, the ratio of the surface area of the modified platinum particles to the total surface area of the platinum particles (surface modification rate) is determined by using the hydrogen adsorption current value of the reduction wave in the cyclic voltammogram.
[0100] Table 1 shows the characteristics of the carbon support for the catalysts in Examples 1-7 and Comparative Examples 1-7, and the evaluation results of the catalysts. Additionally, Figure 1 The relationship between the mode particle size of the primary particles of the carbon support for the catalysts of Examples 1 to 7 and Comparative Examples 1 to 4 and the rate of increase in the mass activity of the catalysts is shown. Figure 2 The relationship between the median particle size of the primary particles of the carbon support for the catalysts of Examples 1 to 7 and Comparative Examples 1 to 4 and the rate of increase in the mass activity of the catalysts is shown.
[0101] [Table 1]
[0102]
[0103] As shown in Table 1 (Examples 1-7 and Comparative Examples 1-4), the smaller the mode particle size and median particle size of the primary particles of the carbon support, the higher the surface modification rate.
[0104] As shown in Table 1 and Figure 1 As shown, the smaller the modal particle size of the primary particles of the carbon support, the higher the rate of increase in catalyst activity. In particular, the catalysts of Examples 1 to 7, in which the modal particle size of the primary particles of the carbon support is less than 700 nm, show a higher catalyst activity improvement effect compared with the catalysts of Comparative Examples 1 to 4, in which the rate of increase in mass activity exceeds 1.0 and the modal particle size of the primary particles of the carbon support exceeds 700 nm.
[0105] As shown in Table 1 and Figure 2 As shown, the smaller the median particle size of the primary particles of the carbon support, the higher the rate of increase in the mass activity of the catalyst. In particular, the catalysts of Examples 1 to 7, with a median particle size of the primary particles of the carbon support of less than 750 nm, showed a higher catalyst activity improvement effect compared with the catalysts of Comparative Examples 1 to 4, which had a mass activity improvement rate of more than 1.0 and a median particle size of the primary particles of the carbon support of more than 750 nm.
[0106] The BET specific surface area, mode pore size, and total pore volume of the carbon support of the catalysts in Comparative Examples 5 to 7 are outside the range of values specified for the electrochemical oxygen reduction catalyst according to one aspect of the present invention. As shown in Table 1, although the catalysts of Comparative Examples 5 to 7 have a high rate of improvement in mass activity, they have low battery voltage and low catalyst activity.
[0107] Furthermore, the present invention is not limited to the described embodiments and includes various modifications. For example, the described embodiments are examples provided for ease of understanding and illustration of the invention, and are not limited to having all the described structures. Additionally, with respect to a portion of the structure of each embodiment, other structures can be added, deleted, and / or replaced.
Claims
1. An electrochemical oxygen reduction catalyst, comprising: an oxygen reduction active catalyst metal supported on mesoporous carbon; and a modifying layer modifying said catalyst metal. in, The primary particle size of the mesoporous carbon is below 700 nm. The mesoporous carbon satisfies at least one of the following a) to c): a) BET specific surface area is greater than 641m² 2 g -1 ; b) The mode aperture is less than 7.7 nm; c) The total micropore capacity of pores in the range of 2.0 nm to 30 nm is greater than 6.50 mL g. -1 .
2. The electrochemical oxygen reduction catalyst according to claim 1, wherein the mode particle size of the primary particles of the mesoporous carbon is less than 300 nm.
3. An electrochemical oxygen reduction catalyst, comprising: an oxygen reduction active catalyst metal supported on mesoporous carbon; and a modifying layer modifying said catalyst metal. in, The median particle size of the primary particles of the mesoporous carbon is below 750 nm. The mesoporous carbon satisfies at least one of the following: a) to c) a) BET specific surface area is greater than 641m² 2 g -1 ; b) The mode aperture is less than 7.7 nm; c) The total micropore capacity of pores in the range of 2.0 nm to 30 nm is greater than 6.50 mL g. -1 .
4. The electrochemical oxygen reduction catalyst according to claim 3, wherein, The median particle size of the primary particles of the mesoporous carbon is below 400 nm.
5. The electrochemical oxygen reduction catalyst according to claim 1 or 3, wherein, The catalyst metal is platinum, a platinum alloy, or a platinum-containing composite, and the modification layer contains a nitrogen-containing cyclic organic compound or a polymer thereof or their cations.
Citation Information
Patent Citations
Catalyst
JP2024011754A
Catalyst
JP2024016321A